Digital affordances: how entrepreneurs access support in online communities during the COVID-19 pandemic - Marie Madeleine Meurer; Matthias Waldkirch; Peter Kalum Schou; Eliane Léontine Bucher; Katrin Burmeister-Lamp (Small Business Economics, 2021)
COVID-19 has caused significant and unforeseen problems for entrepreneurs. While entrepreneurs would normally seek social support to help deal with these issues, due to social distancing, physical networks are often not available. Consequently, entrepreneurs must turn to alternative support sources, such as online communities, raising the question of how support is created in such spaces. Drawing on an affordance perspective, we investigate how entrepreneurs interact with online communities and base our qualitative analysis on conversation data (76,365 posts) from an online community of entrepreneurs on Reddit during the COVID-19 pandemic. Our findings draw out four affordances that online communities offer to entrepreneurs (resolving problems, reframing problems, reflecting on situations, refocusing thinking and efforts), resulting in a framework of entrepreneurial support creation in online communities. Thus, our study contributes to debates around (1) entrepreneurs' support during COVID-19 and (2) digital affordances in the entrepreneurship context.
Keywords: L26; M10; M13; 330; Entrepreneurial support; Online communities; Affordances; COVID-19; Big data